When Feeling Mixed Can Be Meaningful: The Relation Between Mixed Emotions and Eudaimonic Well-Being - Berrios-Espinoza, R (Springer Netherlands, 2018)
Whilst positive emotions benefit well-being, the role of other more complex emotional experiences for well-being is less well understood. This research therefore investigated the relationship between mixed emotions and eudaimonic well-being. A cross-sectional study (Study 1; N = 429) first demonstrated (using structural equation modelling) that mixed emotions are related to the presence of goal conflict. Importantly, it was also found that mixed emotions are positively related to eudaimonic well-being, and that one potential mechanism linking mixed emotions and eudaimonic well-being is via the search for meaning in life. Study 2 (N = 52) implemented a quasi-experiment regarding a naturally occurring meaningful life event (i.e., graduation day) and again demonstrated that mixed emotions are associated with a greater level of eudaimonic well-being. Implications of these findings include the importance of mixed emotions in the search for meaning in life, and the role of mixed emotions in goal conflict resolution. © 2017, Springer Science+Business Media Dordrecht.